Temporal valuation of corn respiration rates using pressure sensors. (March 2015) - Ubhi, Gagandeep Singh; Sadaka, Sammy
Abstract: Proper grain management requires chronological and precise measurements of carbon dioxide evolved from grain respiration during the postharvest storage duration. The main goal of this research was to develop a new technique that evaluates temporal corn respiration rate using pressure sensors. The effects of corn storage temperature (23, 35, and 45 °C) and initial moisture content (12.9, 14.8, 17.0, 18.8, and 20.7% w.b) on the cumulative respiration were studied for duration of nine days. Additionally, the established technique was used to develop an empirical equation to predict the corn respiration rate as affected by storage temperature, moisture content, and storage duration. The pressure sensor method was found to be reliable in measuring corn respiration rate as affected by the tested parameters. The highest cumulative respiration of 2.625 g/kg was observed with the moisture content of 18.8% and the medium temperature level of 35 °C after nine days. Increasing and/or decreasing the moisture content level from 18.8% negatively affected the cumulative respiration. Respiration rates reached their maximum values of 0.199, 0.755, 0.987, and 1.147 g/kg.d under the medium temperature level of 35 °C and the moisture contents of 14.8% (5th day), 17.0% (5th day), 18.8% (3rd day), and 20.9% (2nd day), respectively. The logarithmic value of the corn cumulative respiration was positively correlated with the initial moisture content values, the storage temperature, and the storage duration with an adjusted coefficient of determination value of 0.80. Highlights: A reliable technique was developed to measure corn respiration continuously. Corn respiration rates under 35 °C were higher than that under other temperature levels. An empirical equation was developed to predict corn cumulative respiration.